The power of standards : hybrid authority and the globalisation of services - Graz, Jean-Christophe (New York : Cambridge University Press, 2019)
"Standards often remain unseen, yet they play a fundamental part in the organisation of contemporary capitalism and society at large. What form of power do they epitomise? Why have they become so prominent? Are they set to be as important for the globalisation of services as for manufactured goods? Graz draws on international political economy and cognate fields to present strong theoretical arguments, compelling research and surprising evidence on the role of standards in the global expansion of services, with in-depth studies of their institutional environment and cases including the insurance industry and business process outsourcing in India. The power of standards resembles a form of transnational hybrid authority, in which ambiguity should be seen as a generic attribute, defining not only the status of public and private actors involved in standardisation and regulation, but also the scope of issues concerned and the space in which such authority is recognised when complying to standards. This book is also available as Open Access"--
"According to the quotation above taken from the flagship publication of the International Organization for Standards (ISO), there is an upfront rationale for standards supporting the services sector's contribution to growth and development. In the same way as manufacturing is inconceivable without standardized bolts and nuts, it is difficult to imagine providing services across borders without proper guarantees regarding the quality and security of the activity expected to be performed to the customer satisfaction. From this view, standards appear as promising tools against the backdrop of the growing share of services in globalisation. Be it an airline's customer service centre located in the Philippines, legal process outsourcing in India in charge of drafting contracts for law firms in London, reliability of data on natural hazards in Japan supposedly hedged by reinsurance companies in the United States and Europe, or more prosaically requirements for services provided by natural protected areas authorities or multinational water utility firms -- all these are expected to be specified in mutually intelligible and agreed terms"--
Machine generated contents note: Introduction; 1. The rise of transnational hybrid authority: a primer; 2. Service offshoring: the new frontier of globalisation; 3. Standards as regulation; 4. Doubling security: prudential standards for insurance regulation; 5. Standards to create new insurance markets; 6. The world office; 7. Standards and business process outsourcing in India; Conclusions.
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE / International Relations / General; Service industries; Service industries -- Standards; Globalization; Standardization